Agile Internal Audit from the Perspectives of Saudi Internal Auditors: An Exploratory Study - Almahyawi, Anan Abdulaziz; Alsudairi, Fahdah Sultan (Journal of Economic, Administrative and Legal Sciences, 2023)
This research explores the concept and principles of agile internal audit and the views of Saudi internal auditors regarding the expected obstacles and challenges of applying this approach, in addition to their perspectives on the extent to which their organizations support the adoption of the agile methodology in internal auditing. This qualitative study employed exploratory analytical methodology by analyzing the data from 25 interviews with Saudi internal auditors using the thematic analysis method. The research concluded several results, the most important of which is that the obstacles to implementation are the lack of awareness of the concept of agile internal auditing among auditors and stakeholders and the need to gain the support of organizations by providing the financial and human resources and technical tools necessary to adopt the agile methodology to internal auditing. The organization’s culture also plays an essential role in developing the internal audit function to become more efficient and effective. Considering the previous results, the study presented several recommendations, most notably the need to raise auditors’ awareness of the importance of agile internal auditing and its advantages and benefits, clarifying its practical applications, and conducting more research on agile methodology and its applications in internal audit.